Psoriasin has divergent effects on the innate immune responses of murine glial cells. Issue 1 (27th February 2017) - Jansen, Sandra; Kress, Eugenia; Fragoulis, Athanassios; Wruck, Christoph J.; Wolf, Ronald; Grötzinger, Joachim; Michalek, Matthias; Pufe, Thomas; Tauber, Simone C.; Brandenburg, Lars‐Ove
Abstract: Antimicrobial peptides are an important part of the innate immune defense in the central nervous system (CNS). The expression of the antimicrobial peptides psoriasin (S100A7) is up‐regulated during bacterial meningitis. However, the exact mechanisms induced by psoriasin to modulate glial cell activity are not yet fully understood. Our hypothesis is that psoriasin induced pro‐ and anti‐inflammatory signaling pathways as well as regenerative factors to contribute in total to a balanced immune response. Therefore, we used psoriasin‐stimulated glial cells and analyzed the translocation of the pro‐inflammatory transcription factor nuclear factor 'kappa‐light‐chain‐enhancer' of activated B‐cells (NFκB) in murine glial cells and the expression of pro‐ and anti‐inflammatory mediators by real time RT‐PCR, ELISA technique, and western blotting. Furthermore, the relationship between psoriasin and the antioxidative stress transcription factor nuclear factor erythroid 2‐related factor 2 (Nrf2) was investigated. Stimulation with psoriasin not only enhanced NFκB translocation and increased the expression of the pro‐inflammatory cytokines, interleukin‐6 (IL‐6) and tumor necrosis factor‐α (TNF‐ α) but also neurotrophin expression. Evidence for functional interactions between psoriasin and Nrf2 were detected in the form of increased antioxidant response element (ARE) activity and induction of Nrf2/ARE‐dependent heme oxygenase 1 (HO‐1) expression in psoriasin‐treated microglia and astrocytes. The results illustrate the ability of psoriasin to induce immunological functions in glia cells where psoriasin exerts divergent effects on the innate immune response. Abstract : Antimicrobial peptides (AMPs) are an important part of the innate immune defense in the central nervous system (CNS). The antimicrobial peptide, psoriasin, modulates glial cell activity, but the exact underlying mechanisms are not yet fully understood. We show that psoriasin not only induced pro‐inflammatory cytokines, but also neurotrophin expression. In addition, we detected functional interactions between psoriasin and the antioxidative stress transcription factor nuclear factor erythroid 2‐related factor 2 (Nrf2). The induction of Nrf2‐dependent anti‐inflammatory enzyme heme oxygenase 1 (HO‐1) could contribute to the antioxidative and anti‐inflammatory properties of psoriasin.